Peau: à propos de sexe, de classe et de littérature - Allison, Dorothy.. (Sorcières, 2015)
Activiste féministe lesbienne radicale depuis les années 1970, Dorothy Allison a connu le succès avec ses romans (L’Histoire de Bone, Retour à Cayro). En 1994, elle publie Peau, un recueil d’essais. Elle y parle de son enfance, d’inceste, de lesbophobie. Elle raconte son engagement féministe, sa sexualité, les « Sex Wars » des années 1980. Elle partage ses réflexions sur la littérature : comment écrire l’extrême misère sociale, comment écrire sur le sexe ? Un livre tout à la fois intime, décapant et profondément politique, réédité avec sept textes inédits en français.
Keywords: amériques; approches et analyses; arts; cours; discipline; discours dominant; fem1300; histoire et politique; lesbianisme; militance; personnes lesbiennes; premier cycle; privilèges; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail du sexe; états-unis; études littéraires

Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"--Page 4 de la couverture.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art